ANALISIS WACANA KRITIS NORMAN FAIRCLOUGH PADA PEMBERITAAN DEMO MAHASISWA TOLAK REVISI RKUHP DAN UU KPK DI KOMPAS TV - Amalia, Anisa; Syukron, Akhmad Aufa (Universitas Sriwijaya, 2020)
Kompas.com tries to lead readers' opinions that as news aggregator media, they always follow the development of social issues that occur around Indonesian society. Kompas.com is an online news program that publishes many news updates, one of which is currently hot about student demonstrations rejecting the revision of the RKUHP and the RUU KPK, viewed from a variety of discourse packages. In the study of discourse analysis, Norman Fairclough's discourse analysis model is one of the models that views language with regard to representation, relations, identity and socio-culture. The analysis of this study uses microstructural analysis, mesostructural and macrostructural analysis. This type of research is descriptive qualitative, with the method of observation as data collection. The results showed that the news in kompas.com used language in the case of student demonstrations rejecting the revision of the RKUHP and the RUU KPK in a light, concise and easily understood way from the political elite, academics, state officials and the public.